Poverty eradication in the light of Quran and Sunnah: a maqassid approach - Zakariyah, Habeebullah; A Maikabara, bdullateef Abdulqadir (Al-Hikmah Research & Publication Center, 2020)
The evolution of poverty has been an emerging economic and social phenomenon which poses the attention of national and international government and developmental organizations in Muslim and non-Muslim countries to initiate various strategies and programs for the poverty alleviation. In Islam, it is crucially important to cater for the wellbeing of the people in a society so that it would positively constitute socioeconomic development, political stability and religion propagation. This study aims to explore the poverty alleviation measures prescribed in Islam as a collective solution to several calamities. For this purpose, deductive research method is adopted to articulate the major maqassid of Quran and Sunnah in eradicating poverty as the two primary sources of Shariah explicitly and implicitly encompass all the aspects of life most especially the livelihood wellbeing in accordance with Shariah objective of wealth protection. The study is significant as it will revive Muslims’ intuition to refer back to the teachings from the divine sources to ensure socio-economic development and sustainability.